Direito humanos e desenvolvimento: uma análise do exercício de liberdade religiosa nas relações de trabalho - Gaudêncio, Isabelly Cristinny Gomes (2017)
The purpose of this study is to analyze the exercise of religious freedom in labor relations under the human rights approach, based on the principle of the dignity of the human person, inserted as the core of the constitutional and international protection granted to Brazilian citizens and the world. In this way, mechanisms must be inserted that guarantee access and provide the religious freedom of workers, giving dignity in the working relationship. Therefore, this work is classified as an explanatory research, because it aims to explain the phenomenon religious freedom in the most diverse situations, with a qualitative methodological approach, since it was necessary to collate the opinion of several authors, contrasting their points of view, until reaching the Its outcome. In addition, the method of approach is deductive, since part of the general analysis of religious freedom for specific, religious freedom in labor law, using the method of exegetical interpretation, whose premise is the Universal Declaration of Human Rights , As well as the Federal Constitution of 1988 and the lesser fact the doctrinal lectures, having, as a technical procedure, the bibliographical and the research technique of indirect documentation, since the research was developed based on materials already elaborated, Various authors, mainly composed of books.